PENGARUH PEMBELIAN IMPULSIF TERHADAP KECEMASAN KONSUMEN YANG BERDAMPAK PADA PEMBELIAN KOMPULSIF DAN DIMEDIASI OLEH ESKAPISME (Studi Kasus Pada Matahari Departement Store Di Banda Aceh) - Fitria Muchnisa; Sulaiman Sulaiman (Departemen Manajemen, 2020)
This study aims to examine the effect of Impulsive buying Influence on Consumer Anxiety That Affects to Compulsive buying and Mediated By Eskapisme investigated at Matahari Department Store in Banda Aceh. The sampling method in this study uses purposive sampling with a sample of 100 respondents. Data analysis method used is simple regression and Path Analysis. The results showed that impulsive buying had a positive and significant effect on consumer anxiety, consumer anxiety had a positive and significant effect on escapism, escapism had a positive and significant effect on compulsive Buying and consumer anxiety had a positive and significant effect on compulsive Buying. Mediation testing shows that the Escapism variable mediates the relationship between Consumer Anxiety and Compulsive Buying.